Simulation de Ia propagation de fissures dans les solides elastiques en modes mixtes par Ia methode des equations integrales duales - Kebir, Hocine; Roelandt, Jean Marc; Gaudin, Jocelyn (European Journal of Computational Mechanics, 2000)
The present paper is concerned with the effective numerical implementation of the two dimensional Dual Boundary element method to analyse the mixed-mode crack growth All the boundaries are discretized with discontinuous quadratic boundary elements and the crack-tip is modeled by singular elements that exactly represent the strain field singularity 1/ ..fi The Stress Intensity Factors can be computed very accurately from the crack opening displacement at collocation points extremely close to the crack tip The algorithm is applied to several two dimensional examples and the results obtained are in very good agreement with experimental results.